Bangladesh Rural Advancement Committee - financial statements December 31, 1997 : together with independent auditor's report - BRAC (© BRAC, 2016)
This Financial Statement prepared by Arthur Andersen & Co. Chartered Accountants, Dubai - United Arab Emirates and Acnabin & Co. Chartered Accountants, National Scout Bhaban (13th floor), 70/1 Inner Circular Road, Kakrail, Dhaka- 1000, Bangladesh